Otimização e validação da técnica de extração sólido-líquido com purificação em baixa temperatura de dibenzo-p-dioxina e dibenzofurano policlorados em lodo de esgoto e solo - Valeria Farias Andrade (2015)
Sewage sludge is a solid residue generated during the treatment ofwastewater in Sewage Treatment Plants (STPs). After treated and processed, this material can be used in agriculture as a complement to fertilizer or conditioner of agricultural soils due to the high content of organic material as well as essential elements to plants, such as nitrogen and phosphorus. However, this practice can lead to contamination and accumulation of toxic pollutants and pathogenic micro-organisms in soil, plants and animals, as well as enter the food chain or be transported to rivers or even groundwater. In the present work, the solid-liquid extraction technique with purification at lowtemperature (ESL-PBT) was optimized and validated for monitoring of 2,3,7,8- tetrachlorodibenzo-p-dioxin (2,3,7,8 -TCDD) and 2,3,7,8-tetraclorodibenzenofurano (2,3,7,8-TCDF) in sewage sludge and soil. The analyzes were performed by gas chromatography coupled to massspectrometry. For the extraction of these compounds it was used acetonitrile / ethyl acetate (6.50 mL: 1.50 mL). The extraction percentages were higher than 97% with relative standard deviation of less than 5% for sewage sludge and above 82% with relative standard deviation of less than 7% for soil at the limit of quantitation (LOQ). The LOQ for the sewage sludge were 1.6 ngkg-1 TEQ for 2,3,7,8-TCDF and 8 ngkg-1 TEQ of 2,3,7,8-TCDD in sewage sludge. Already in the soil the LOQ were of 0.2 ng kg-1 TEQ for the 2,3,7,8-TCDF and of 2 ng kg-1 TEQ of 2,3,7,8-TCDD. The method presented itself linear in the studied concentration range (between 1.25 to 25 g L-1 for sewage sludge and from 1.25 to 20 g L-1 for ground), selective, accurate and precise. Being a viable alternative to the monitoring of 2,3,7,8-TCDD and 2,3,7,8-TCDDF in sewage sludge and soil for agricultural destination.